Respiratory syncytial virus infection and novel interventions - Langedijk, Annefleur C.; Bont, Louis J. (Nature reviews. Microbiology, 2023)
The large global burden of respiratory syncytial virus (RSV) respiratory tract infections in young children and older adults has gained increased recognition in recent years. Recent discoveries regarding the neutralization-specific viral epitopes of the pre-fusion RSV glycoprotein have led to a shift from empirical to structure-based design of RSV therapeutics, and controlled human infection model studies have provided early-stage proof of concept for novel RSV monoclonal antibodies, vaccines and antiviral drugs. The world’s first vaccines and first monoclonal antibody to prevent RSV among older adults and all infants, respectively, have recently been approved. Large-scale introduction of RSV prophylactics emphasizes the need for active surveillance to understand the global impact of these interventions over time and to timely identify viral mutants that are able to escape novel prophylactics. In this Review, we provide an overview of RSV interventions in clinical development, highlighting global disease burden, seasonality, pathogenesis, and host and viral factors related to RSV immunity. In this Review, Langedijk and Bont discuss our current understanding of respiratory syncytial virus (RSV) burden of disease, virus biology and pathogenesis, and host and viral factors related to immunity as a segue towards the development of novel RSV interventions.